Determinants of foreign direct investment modes and their impact on export performance and economic growth in ASEAN countries - Moghadam, Alireza Tavakol (2020)
Foreign Direct Investment is seen as an essential source of physical capital and intangible assets, such as technical knowledge and managerial skills for economic development in developing countries. Meanwhile, the ASEAN region has become one of the most significant places for attracting FDI into developing countries. However, the trends of FDI and its modes in the region vary across countries and fluctuate over time. Nevertheless, most scholars have focused on aggregate FDI, and there are limited studies conducted on FDI and its entry modes, and their implications on export performance and economic growth in the ASEAN region. Regarding different nature of modes, this study aims to fill the information gap by decomposing FDI into two modes: a) Merger and Acquisition (M&A), and b) Greenfield investment, investigating their determinants and impacts of modes on selected ASEAN countries’ export performance and economic growth. The main six countries in the region include Indonesia; Malaysia; Philippines; Singapore; Thailand and Vietnam (ASEAN- 6) were selected for this study mainly due to the lack of information about other ASEAN members. To achieve all the objectives of this thesis, panel Pooled Mean Group (PMG) of dynamic estimations and the same sample period from 1990 to 2016 were used. The sample period of this thesis began in 1990, the year that the statistics of FDI started. The first objective of this thesis is to examine the determinants of FDI entry modes, namely, merger and acquisition (M&A) and Greenfield. The main findings of the first objective demonstrate that market size, trade openness as a proxy of trade liberalization and human capital are positively related to Greenfield inflows. However, the exchange rate as a representative of financial stability and infrastructure have adverse effects on Greenfield. Moreover, market size inversely affects cross-border merger and acquisition (M&A) sales, although trade openness and exchange rate are positively related to this entry mode. Therefore, the larger market size, more trade liberalization, larger the human capital and additional financial stability would encourage Greenfield inflows. In contrast, smaller market size, weaker financial stability, and more trade liberalization promote M&A sales in the case of ASEAN-6 countries. Indeed, with an increase in market size for the ASEAN-6 countries, the local firm owners are less likely to sell their companies to foreign parties and vice versa. Moreover, the depreciation of local currencies in the group makes the host firms cheaper and leads to more M&A sales while this causes less Greenfield investment due to a decrease in the benefits of MNEs in the host countries. Furthermore, more trade openness as a proxy of trade liberalization facilitates import raw materials and machinery as inputs and export of final goods in easing ways that positively affects both entry modes. The second objective of this thesis is to investigate the effects of FDI entry modes on export, and the results show that both FDI entry modes have significant effects on export performance. Besides, the Gross Domestic Product per capita growth has a profoundly positive relationship to export. Thus, more FDI inflows and rapid economic growth increase export in the region. Greenfield, as a source of physical capital, new technology, and knowledge, creates additional capacity that enhances competitiveness and productivity, leading to more export. Moreover, M&A links the local market to the global distribution network that enhances competitiveness and productivity in the host countries and leads to a rise in export. In the third objective, we examine the effects of FDI entry modes on economic growth. The findings reveal that the relationship between FDI entry modes and economic growth is positive and statistically significant. More precisely, the findings demonstrate that the M&A appears to hold a more impact on economic growth than Greenfield. Besides, gross fixed capital formation as a representative of domestic investment positively associated with growth. Therefore, more Greenfield inflow and M&A sales and additional domestic investment lead to economic growth in the case of ASEAN-6 countries. Gross fixed capital formation, as a proxy of domestic investment and as a complementary to foreign investment, improves economic development. Moreover, this component had the most significant impact on growth for this particular group of countries. Overall, the findings of this thesis provide a thorough understanding of the determinants of FDI modes and their impacts on the macroeconomic performance of ASEAN-6 countries. Thus, efforts geared towards improving one may adversely affect the other. Hence, we recommend for governments of the ASEAN-6 countries to identify which inflows of FDI should be the focus of their countries, and formulate their policies accordingly.